Neutron activation analysis on sediments from Victoria Land, Antarctica: multi-elemental characterization of potential atmospheric dust sources - Baccolo, G.; Baroni, C.; Clemenza, M.; Delmonte, B.; Maggi, V.; Motta, A.; Nastasi, M.; Previtali, E.; Salvatore, M. C. (Journal of Radioanalytical and Nuclear Chemistry, 2014)
The elemental composition of 40 samples of mineral sediments collected in Victoria Land, Antarctica, in correspondence of ice-free sites, is presented. Concentration of 36 elements was determined by instrumental neutron activation analysis, INAA. The selection of 6 standard reference materials and the development of a specific analytical procedure allowed to reduce measurements uncertainties and to verify the reproducibility of the results. The decision to analyze sediment samples from Victoria Land ice-free areas is related to recent investigations regarding mineral dust content in the TALos Dome ICE core (159 degrees 11'E; 72 degrees 49'S, East Antarctica, Victoria Land), in which a coarse local fraction of dust was recognized. The characterization of Antarctic potential source areas of atmospheric mineral dust is the first step to identify the active sources of dust for the Talos Dome area and to reconstruct the atmospheric pathways followed by air masses in this region during different climatic periods. Principal components analysis was used to identify elements and samples correlations; attention was paid specially to rare earth elements (REE) and incompatible/compatible elements (ICE) in respect to iron, which proved to be the most discriminating elemental groups. The analysis of REE and ICE concentration profiles supported evidences of chemical weathering in ice-free areas of Victoria Land, whereas cold and dry climate conditions of the Talos Dome area and in general of East Antarctica.